High-Pressure Natural Gas Pipeline in Geohazard Region of Papua New Guinea Sustains Mw7.5 Earthquake: Key Factors of Successful Outcome - Albrecht, Robert; Calame, John; Cook, Mike; Falcon, Ignacio; Lee, Patrick (2020)
Abstract ExxonMobil PNG Limited (EMPNG) operates the Papua New Guinea Liquefied Natural Gas Project (PNG LNG), an integrated LNG project comprising wellpads, gathering lines, gas conditioning plant, onshore and offshore export pipelines, liquefaction plant and marine terminal in Papua New Guinea (PNG). The PNG LNG project is a joint venture with participation by ExxonMobil, Oil Search Limited (OSL), Kumul Petroleum, Santos, JX Nippon Oil and Gas Exploration and Mineral Resources Development Company, and began production in 2014. The highlands of PNG presents a challenging physical environment, with high rainfall, steep terrain, active tectonics and seismicity, and ongoing landsliding and erosion. The PNG LNG onshore gas and condensate pipelines confront these physical challenges by having to traverse approximately 150 km of steep volcanic, mudstone and Karstic highlands along the Papuan Fold and Thrust Belt, the modern leading edge of active mountain-building, plus an additional 150 km in Karstic lowlands. During design, construction and operations of the pipelines, ExxonMobil has addressed these challenges in partnership with the engineering, construction and specialist consulting communities. On February 25th, 2018 (UTC) a Magnitude 7.5 earthquake struck the PNG highlands. The event, along with its approximately 300 aftershocks, caused widespread community impact, landsliding and damage to over 1000s of km2, and was centered directly under the highlands portion of the PNG LNG pipelines. The pipelines however, did not lose containment or pressure, and, following inspections and repairs to the PNG LNG gas conditioning plant, PNG LNG production was restored within seven weeks of the main shock. This technical paper and companion oral presentation discuss the key factors of this successful outcome, in particular the sustained condition of the gas and condensate pipelines. Contributing factors to the pipeline’s success include route selection, pipe material specification, early commitment to field studies, careful assessment of geohazards, high awareness of off-ROW community impacts, micro-routing during construction, and active geohazard management during startup and operations. The paper demonstrates that, with respect for the host community, thoughtful engineering, careful construction and ongoing surveillance, pipelines can be safely and successfully designed, constructed and operated in remote and extreme geohazardous environments.
openalex: W3121815731 mag: 3121815731
Keywords: openalex:import

Papua New Guinea Earthquake Proves the Value of Robust Pipeline Materials Selection and Construction - Macia, M.L.; Crapps, Justin M.; Noecker, Fredrick F.; Nissley, N. E.; Cook, Mike (2021)
openalex: W4239948147
Keywords: openalex:import